The Prospect of Sharia Banking Industry Development in Indonesia and Malaysia - Ghozali, Habib M (International Conference of Moslem Society, 2018)
Sharia banking industry thrives in various countries in the world. It develops not only in Muslim-majority countries but also in various Muslim-minority countries. The growth of sharia banking assets is generally 50% faster than the growth of the world financial industry market. Indonesia and Malaysia are the two countries in the Southeast Asian region the sharia banking development rates of which are very fast. Until the end of 2017 its growth can reach 50%. There are some efforts done by both countries to boost the rate of movement. For instance, the sharia banking institutions in Indonesia are targeting approvals in various regulations, in addition to improving services, as well as expanding network expansion. While in Malaysia, the strategy is done through strengthening infrastructure, increasing human resources, and also the application of moderate Islamic understanding. The sharia banking industry in each of these two countries has advantages and bright future prospects. More especially, Indonesia has wider potential of the region and larger population. Therefore, the future development of sharia banking industry is much more promising.